ANALISIS KINERJA PENDAPATAN ASLI DAERAH KABUPATEN BATANGHARI 2012-2016 - Jasasila Jasasila (Universitas Batanghari, 2017)
This Penetilian formulate the problem how the Performance of Kabupaten Batanghari Original Income for the period 2012-2016 with the scope of the discussion, PAD Development, PAD Effectiveness and Financial Independence Kabupaten Batanghari during 2012-2016, while the purpose of this study to determine the performance of the original income of Batanghari seen from the development of PAD, PAD Effectiveness and Regional Financial Independence. The type of data used in this study is a collection of information or facts recorded through direct observation while the data used sourced from relevant agencies related to research topics to get the performance of the original income of Kabupaten Batanghari 2012-2016 the authors do the analysis by using analysis of the development of PAD, Analysis of effectiveness and independence analysis. From the results of the analysis obtained the result that the development of PAD Kabupate Batanghari from 2012 to 2016 is fluctuating, where the largest increase occurred in 2014 that amounted to 39.87%, but in 2015 there was a decrease in realization of PAD by 2.65%, this decrease one of which is caused by the realization of Pajak Bumi Bangunan (PBB) revenues of rural and urban sector in Kabupaten Batanghari 2015 decreased as the impact of falling prices of oil palm and rubber. This Pajak Bumi Bangunan (PBB) compulsory reduction is based on Pajak Bumi Bangunan realized revenue per kecamatan from January to September 2015. For the effectiveness of PAD Kabupaten Batanghari shows that in 2012, 2015 and 2016 are categorized quite effectively with the calculation of 84%, 85% and 82%, respectively in 2013 and 2014 respectively 110% and 103% are categorized as very effective, from the calculation result according to the interval scale, financial independence of Kabupaten Batanghari is below 10%, it means that financial independence of Kabupaten Batanghari is very less.Keywords: Performance, PAD, Development, Effectiveness, Independence